Bridging to Caring Economics and a Changed World - Donald Gault (Interdisciplinary Journal of Partnership Studies)
Bridging is a furniture bank located in Minnesota’s Twin Cities.  Since 1987, Bridging has helped make the homes of close to 350,000 people places of dignity and hope. The work of Bridging is built around a remarkable series of partnerships that strongly aligns with Riane Eisler’s concept of caring economics, and Bryan Stevenson’s challenge to us all to take action to change the world. This paper will outline the origins of Bridging, how it operates, and how it represents an inspiring, tangible example of the power of partnership to transform individuals and communities.